Electronics and Signal Processing Selected Papers from the 2011 International Conference on Electric and Electronics (EEIC 2011) in Nanchang, China on June 20-22, 2011, Volume 1 - Hu, Wensong (Lecture Notes in Electrical Engineering, 2011)
This volume includes extended and revised versions of a set of selected papers from the International Conference on Electric and Electronics (EEIC 2011) , held on June 20-22 , 2011, which is jointly organized by Nanchang University, Springer, and IEEE IAS Nanchang Chapter.   The objective of EEIC 2011 Volume 1 is to provide a major interdisciplinary forum for the presentation of new approaches from Electronics and Signal Processing, to foster integration of the latest developments in scientific research. 133 related topic papers were selected into this volume. All the papers were reviewed by 2 program committee members and selected by the volume editor Prof. Wensong Hu.   We hope every participant can have a good opportunity to exchange their research ideas and results and to discuss the state of the art in the areas of the Electronics and Signal Processing.